SEROPREVALENCIA DEL VIRUS DE LARINOTRAQUEITIS INFECCIOSA BOVINA EN BOVINOS DE CRIANZA EXTENSIVA EN LA ZONA DE CAJAMARCA - Manchego S., Alberto (2012)
The prevalence of the bovine herpesvirus 1 (BHV-1) was studied in cattle raised under an extensive rearing system andwithout history of vaccination. Herds were located in the province of San Pablo, department of Cajamarca, Peru. Blood samples from 480 bovine were collected for detection of antibodies against BHV-1 by viral neutralization test. The seroprevalence was 0.6 ± 0.7% (3/480). The three positive Holstein cows, older than 6 years, were part of the same herd and the antibody titers were 1:64 (2) and 1:32 (1). The results indicated that the BHV-1 is now widely distributed in cattle of the studied region.